Rusingeria nom. nov, a new substitute name for Usingeria Coetzee & Segerman, 1992 (Hemiptera: Heteroptera: Cimicidae) - Coetzee, Maureen; Kment, Petr (Zootaxa, 2013)
Rusingeria nom. nov. is established as a new substitute name for Usingeria Coetzee & Segerman, 1992 (Hemiptera: Heteroptera: Cimicidae), which is junior homonym of Usingeria Schouteden, 1952 (Hemiptera: Heteroptera: Aradidae). The following new combination is proposed: Rusingeria transvaalensis (Coetzee & Segerman, 1992), comb. nov., for Usingeria transvaalensis Coetzee & Segerman, 1992